Cost-effectiveness of laparoscopic ileocaecal resection versus infliximab treatment of terminal ileitis in Crohn's disease: the LIR!C Trial. Issue 10 (1st February 2019) - de Groof, E Joline; Stevens, Toer W; Eshuis, Emma J; Gardenbroek, Tjibbe J; Bosmans, Judith E; van Dongen, JM; Mol, Bregje; Buskens, Christianne J; Stokkers, Pieter C F; Hart, Ailsa; D'Haens, Geert R; Bemelman, Willem A; et al.
Abstract : Objective: Evaluate the cost-effectiveness of laparoscopic ileocaecal resection compared with infliximab in patients with ileocaecal Crohn's disease failing conventional therapy. Design: A multicentre randomised controlled trial was performed in 29 centres in The Netherlands and the UK. Adult patients with Crohn's disease of the terminal ileum who failed >3 months of conventional immunomodulators or steroids without signs of critical strictures were randomised to laparoscopic ileocaecal resection or infliximab. Outcome measures included quality-adjusted life-years (QALYs) based on the EuroQol (EQ) 5D-3L Questionnaire and the Inflammatory Bowel Disease Questionnaire (IBDQ). Costs were measured from a societal perspective. Analyses were performed according to the intention-to-treat principle. Missing cost and effect data were imputed using multiple imputation. Cost-effectiveness planes and cost-effectiveness acceptability curves were estimated to show uncertainty. Results: In total, 143 patients were randomised. Mean Crohn's disease total direct healthcare costs per patient at 1 year were lower in the resection group compared with the infliximab group (mean difference €−8931; 95% CI €−12 087 to €−5097). Total societal costs in the resection group were lower than in the infliximab group, however not statistically significant (mean difference €−5729, 95% CI €−10 606 to €172). The probability of resection being cost-effective compared with infliximab was 0.96 at a willingness to pay (WTP) of €0 per QALY gained and per point improvement in IBDQ Score. This probability increased to 0.98 at a WTP of €20 000/QALY gained and 0.99 at a WTP of €500/point of improvement in IBDQ Score. Conclusion: Laparoscopic ileocaecal resection is a cost-effective treatment option compared with infliximab. Clinical trial registration number: Dutch Trial Registry NTR1150; EudraCT number 2007-005042-20 (closed on 14 October 2015).